4(a-3)=18+2(3-2a)

Simple and best practice solution for 4(a-3)=18+2(3-2a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a-3)=18+2(3-2a) equation:



4(a-3)=18+2(3-2a)
We move all terms to the left:
4(a-3)-(18+2(3-2a))=0
We add all the numbers together, and all the variables
4(a-3)-(18+2(-2a+3))=0
We multiply parentheses
4a-(18+2(-2a+3))-12=0
We calculate terms in parentheses: -(18+2(-2a+3)), so:
18+2(-2a+3)
determiningTheFunctionDomain 2(-2a+3)+18
We multiply parentheses
-4a+6+18
We add all the numbers together, and all the variables
-4a+24
Back to the equation:
-(-4a+24)
We get rid of parentheses
4a+4a-24-12=0
We add all the numbers together, and all the variables
8a-36=0
We move all terms containing a to the left, all other terms to the right
8a=36
a=36/8
a=4+1/2

See similar equations:

| 12f+3f= | | x=63x–5=10 | | −4x²+4x−1=0 | | 48x-32+2=-30+12x+90x | | (x^2)-18x+61=0 | | 3x+12=5×+16 | | 13x+4=78 | | −2x²+3x−4=0 | | 180=3x+28+5x+52+2x-10 | | x=3x+28+5x+52+2x-10 | | 6-(-5x+4)=2x-8 | | 6-(5x+4)=2x-8 | | 450+22x=1660 | | -2^2+11x-28=0 | | (3x-9)x(2x)=38 | | X-3=2x-87 | | 1+n÷-3=6 | | 1/6x+x+2x=90 | | 4x+40+3=180 | | x+5+(x+1)=12 | | 7(7-4x)=38+x | | 9+6n=-3(4+5n) | | 2/3x-1/6=0 | | 3(-5n-8)=36-5n | | 2/3x+5/6=1 | | -12x-5=-4x+19 | | 2x=+8=16 | | -2x-18=-6x-10 | | -2x-18=-6x | | 7–4x=14+3x | | -6-n=-3(n-6)-n | | 6(1+2x)-x=-7-2x |

Equations solver categories